THE ROLE OF FORUM BANGUN ACEH (FBA) IN COMMUNITY EMPOWERMENT BASED ON SOCIAL INCLUSION THROUGH THE INGIN MAJU COMMUNITY SELF-HELP GROUP (KSM) IN GAMPONG LUTHU DAYAH KRUENG - ACEH BESAR - Rifqi, Muhammad; Situmeang, Marini Kristina; Mahmuddin, Mahmuddin; Murdani, T. (JURNAL AL-IJTIMAIYYAH, 2024)
Community empowerment based on social inclusion through Community Self-Help Groups (KSM) is a step to empower vulnerable communities carried out openly and voluntarily for all communities without exception to ensure that people can fulfill their rights to their living needs and live independently. The purpose of this research is to determine the process of forming KSM in Luthu Dayah Krueng Village, to find out the role of the Forum Bangun Aceh (FBA) in implementing inclusive community empowerment through KSM in Luthu Dayah Krueng Village, and to find out the forms of empowerment in KSM in Luthu Dayah Krueng Village. This research was conducted using qualitative methods. The data collection techniques used were observation, interviews and documentation. In this study, researchers obtained data sources from 8 respondents who were the subjects of this research, including two coordinators of the Forum Bangun Aceh, 2 Administrators of KSM Ingin Maju, 3 Members of Want to KSM Ingin Maju, and 1 Head of Luthu Dayah Krueng Village. This research shows that empowerment based on social inclusion through KSM is considered more effective in empowering a group. Empowerment based on social inclusion through KSM is open and voluntary for the entire community. The Forum Bangun Aceh has carried out its role as founder, coach, facilitator, and educator in community empowerment based on social inclusion through KSM.